Locus of control, self-efficacy, and the mediating effect of outcome control: predicting course-level and global outcomes in an academic context - AU, Evelyn W. M. (Institutional Knowledge at Singapore Management University, 2015)
Background and Objectives. The current study utilizes Skinner's framework to examine the unique contributions of internal locus of control, self-efficacy, and perceived outcome control over course performance on students' academic experiences. Method. Undergraduate students (N = 225) took part in a longitudinal study and completed two surveys (Time 1: just before their mid-term exams; Time 2: just before their final exam in the same semester). Results. Both locus of control and self-efficacy at Time 1 predicted course-level perceived control over course performance at Time 2. Student-level perceived control over course performance at Time 2 mediated the relationship between self-efficacy at Time 1 and course-level perseverance, course-specific stress, and course enjoyment at Time 2. For global perceived stress and life satisfaction measured at Time 2, both locus of control and self-efficacy at Time 1 had only a direct effect on global perceived stress at Time 2, but only self-efficacy at Time 1 predicted life satisfaction at Time 2. Conclusion. Both locus of control and self-efficacy uniquely contribute to students' academic experiences. Student-level perceived control plays an important mediating role between locus of control and self-efficacy at Time 1, and course-level perseverance, course-specific stress, and course enjoyment at Time 2.